2015
DOI: 10.1155/2015/265187
|View full text |Cite
|
Sign up to set email alerts
|

Castleman Disease of the Parotid Gland: A Report of a Case

Abstract: Castleman disease is an extremely rare benign lymphoproliferative disorder of unknown etiology. It affects the lymphatic chain in anybody region, although the commonest site is the mediastinum. The head and neck region is the second most common site; however, the salivary glands are rarely affected. We report a case of a 29-year-old Asian lady who presented with a 2-year history of an enlarging left parotid mass. Histopathology of the excisional biopsy confirmed the diagnosis of Castleman disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Cervical localization usually involves retropharyngeal or parapharyngeal neck spaces [7]. The location of the disease within the parotid gland is very rare and very few cases have been reported to date [8]. In a recent literature review by Xiao-dong et al [9], only 20 cases of parotid gland involvement were reported, with a significant proportion of affected individuals being young adults, consistent with our case.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Cervical localization usually involves retropharyngeal or parapharyngeal neck spaces [7]. The location of the disease within the parotid gland is very rare and very few cases have been reported to date [8]. In a recent literature review by Xiao-dong et al [9], only 20 cases of parotid gland involvement were reported, with a significant proportion of affected individuals being young adults, consistent with our case.…”
Section: Discussionsupporting
confidence: 87%
“…Cervical localization usually involves retropharyngeal or parapharyngeal neck spaces [7]. The location of the disease within the parotid gland is very rare and very few cases have been reported to date [8]. In a recent literature review by Xiao-dong et al [9],…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, CD is classified clinically as unicentric CD (UCD) or multicentric CD (MCD) and histologically as hyaline vascular variant (HVV) or plasma cell variant (PCV) [3, 4]. CD occurs throughout the body on surfaces such as the chest [5], neck [6], abdomen, pelvis [7], axilla [8], and on rare occasions the lung [9], parotid gland [10], and pancreas [11].…”
Section: Introductionmentioning
confidence: 99%
“…The localized CD only affects a single group of lymph nodes and lymph nodes in the chest or abdomen are affected most often. The mediastinum is the most common site, accounting for 60% of cases and the neck is involved in only 14% [3]. Multicentric CD affects more than a single group of lymph nodes.…”
mentioning
confidence: 99%